The Importance of Corticoids Added to Continued Treatment with Factor VIII Concentrates in the Suppression of Inhibitors in Haemophilia A - Aznar, J A; Jorquera, J I; Peiró, A; Garcia, I (Thrombosis and Haemostasis, 1984)
A protocol is presented to suppress inhibitors in haemophilia A using continued treatment with f. VIII (50 U/kg b.w./day) and fluprednisolone (0.5 mg/kg b.w., for 21 days) until reaching correct in vivo recovery after therapeutic administration.5 high responder patients were treated whose inhibitors were detected at least 2 years before beginning the treatment. The inhibitors were eradicated in 4 patients using continued treatment for between 4 and 24 months. Patient 1 was treated exclusively with factor and the others also with corticoids when the level was 0 B.U. (or 20 B.U., patient 4). The patients began tri-weekly prophylactic treatment and rehabilitation exercises after recovery test normalization. After progressive reduction of the prophylactic treatment they started on demand treatment. After more than 5 months of this treatment no anamnestic response has been detected in any patient, in spite of several factor VIII administrations.
Keywords: Haemophilia A; Inhibitors; Suppression; Massive f. VIII treatment; Corticoids